2007
DOI: 10.1002/ldr.801
|View full text |Cite
|
Sign up to set email alerts
|

Integration of arbuscular mycorrhiza inoculation in hydroseeding technology: effects on plant growth and inter‐species competition

Abstract: Hydroseeding is a technique increasingly used to establish vegetation on large degraded areas, such as large-scale road construction sites and quarries. Native grasses and legume species are used on rehabilitation and restoration projects as a first step in the recovery of such places, prior to the establishment of native forbs and shrubs that occurs at a slower pace. The effect of mycorrhizal inoculation on the development of nine species of grasses and legumes that can be potentially used in restoration proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In a growing literature on the subject, mycorrhizas are seen as useful tools in the restoration of degraded soil, but again, species and site are important factors to consider before undertaking any restoration project using mycorrhizas (e.g. Palenzuela et al 2002;Estaun et al 2007). In certain conditions, the introduction of mycorrhizas at a site may even be detrimental to plant establishment (see Walker et al 2009).…”
Section: Heterogeneity In Resource Supplymentioning
confidence: 99%
“…In a growing literature on the subject, mycorrhizas are seen as useful tools in the restoration of degraded soil, but again, species and site are important factors to consider before undertaking any restoration project using mycorrhizas (e.g. Palenzuela et al 2002;Estaun et al 2007). In certain conditions, the introduction of mycorrhizas at a site may even be detrimental to plant establishment (see Walker et al 2009).…”
Section: Heterogeneity In Resource Supplymentioning
confidence: 99%
“…The experiment evaluated the implications on severely disturbed areas as well under controlled conditions (greenhouse trial). Results revealed that the establishment of a symbiotic relationship improves aboveground plant growth and increases the legumes/grasses ratio (both in the greenhouse and in the field) (Estaun et al, 2007). Another study by Brown et al (1983) measured rhizobium viability in hydroseeding slurries by testing variation in the pH due to fertilizer addition.…”
Section: Human-influenced Biotic Factors Affecting Hydroseedingmentioning
confidence: 99%
“…The BEG 72 isolate of G. intraradices is a native arbuscular fungus isolated from a citrus nursery of the mediterranean area (Camprubí and Calvet 1996). It was and has proved effective in many agricultural and landscape restoration situations (Calvet et al 2001, Estaún et al 2007.…”
Section: Inoculum Productionmentioning
confidence: 99%